The Role of Mass Media in Elections in Indonesia - Nuryanti, Nuryanti (Law Research Review Quarterly, 2018)
After almost two decades of reform, Indonesia is still experiencing a transition to democracy, in almost twenty years Indonesia has found full democratization. Some of the progress that has been gained, such as direct elections and the freedom of mass media, should be appreciated. Elections with mass media cannot be separated from each other. Mass media is a means for the dissemination of programs from prospective leaders, so that the community is expected to have an assessment and not to choose the candidate leader. track record of candidates participating in the election can be easily accessed by the public through mass media. Today the media has the most strategic position and has powerful weapons to influence public opinion and lead people's perceptions according to their goals. The success of the election is inseparable from the role of the media in reporting it. The problem is whether the mass media has been able to carry out its functions as a means of political education for the people of Indonesia and how the role of mass media in elections in Indonesia. Therefore the existence of mass media in elections for the community is very important, namely adding information about elections, can influence the behavior of a voter and be chosen so that it will have an impact on the conditions of the political climate in Indonesia.